Prevalence of HCV-Helicobacter pylori co-infection and its effects on liver function enzymes of patients in Lahore, Pakistan - Bin Wahid, Sohaib; Waqar, Muhammad; Rehman, Zobaria; Wasim, Muhammad; Idrees, Muhammad (BioScientific Review, 2019)
Helicobacter pylori and HCV are the most prevalent pathogens worldwide associated with high rates of morbidity and mortality. This study aimed to determine the prevalence of H. pylori in HCV infected patients and compares changes in liver function tests (LFTs) of both HCV mono-infected and HCV/H. pylori co-infected patients. Eighty-seven participants participated in this study who were first screened for HCV using GeneXpert technology followed by H. pylori antigen stool test. A complete blood count (CBC) analysis and LFTs were performed to determine the impact of HCV and H. pylori on liver enzymes. Our findings suggested that 45% of patients had HCV mono-infection, whereas 55% were co-infected with both HCV and H. pylori. Furthermore, we also observed that ALT, AST, and ALP levels were significantly elevated in HCV/H. pylori co-infected patients as compared to HCV mono-infected patients. To the best of our knowledge, this is the first study to report the prevalence of H. pylori in HCV infected subjects of Lahori population